Autonomous and intercellular chemokine signaling elicited from mesenchymal stem cells regulates migration of undifferentiated gastric cancer cells. (16th March 2022) - Okamoto, Daiki; Yamauchi, Natsuko; Takiguchi, Gosuke; Nishita, Michiru; Kakeji, Yoshihiro; Minami, Yasuhiro; Kamizaki, Koki
Abstract: Accumulating evidence demonstrates that bone marrow (BM)‐derived mesenchymal stem cells (MSCs) play critical roles in regulating progression of various types of cancer. We have previously shown that Wnt5a‐Ror2 signaling in MSCs induces expression of CXCL16, and that CXCL16 secreted from MSCs then binds to its cognate receptor CXCR6 on the surface of an undifferentiated gastric cancer cell line MKN45 cells, eventually leading to proliferation and migration of MKN45 cells. However, it remains unclear about a possible involvement of another (other) cytokine(s) in regulating progression of gastric cancer. Here, we show that CXCL16‐CXCR6 signaling is also activated in MSCs through cell‐autonomous machinery, leading to upregulated expression of CCL5. We further show that CCR1 and CCR3, receptors of CCL5, are expressed on the surface of MKN45 cells, and that CCL5 secreted from MSCs promotes migration of MKN45 cells presumably via its binding to CCR1/CCR3. These data indicate that cell‐autonomous CXCL16‐CXCR6 signaling activated in MSCs upregulates expression of CCL5, and that subsequent activation of CCL5‐CCR1/3 signaling in MKN45 cells through intercellular machinery can promote migration of MKN45 cells. Collectively, these findings postulate the presence of orchestrated chemokine signaling emanated from MSCs to regulate progression of undifferentiated gastric cancer cells.